Revitalisasi Misi Kristen Menghadapi Sekularisasi dan Sekularisme: Kasus Gereja Protestan dan Katolik di Belanda - Alexander Djuang Papay; Ferdinandes Petrus Bunthu; Francois Pieter Tomasoa (Sekolah Tinggi Teologi Real Batam, 2020)
This paper is an insight into the revitalization of Christian mission in dealing with secularism in Catholic and Prostestant churches in the Netherlands. Analysis from various collective sources as a consideration to find out how much degradation of the Christian Faith is caused by the influence of secularism and on the other hand also to find out how much influence from the church that still remains. The research used is qualitative descriptive with a literature review, the authors sought the results of this study are expected to help the church to be able to revitalize the Christian mission of secularism in the younger generation, schools within the church environment, evangelism, and contextualization so that the church is expected to return to its heyday. ABSTRAKPaper ini sebagai wawasan tentang revitalisasi misi Kristen dalam menghadapi sekulerisme di gereja-gereja Katolik dan Prostestan di Nederland. Analisis dari berbagai sumber kolektif sebagai pertimbangan untuk mengetahui seberapa besar degradasi Iman Kristen disebabkan oleh sekulerisme dan disisi lain juga untuk mengetahui seberapa besar pengaruh dari gereja yang masih tersisa. Penelitian yang digunakan adalah deskritif kualitatif dengan tinjauan pustaka. Penulis berupaya hasil penelitian ini diharapkan membantu pihak gereja untuk dapat revitalisasi misi Kristen terhadap sekulerisme di generasi muda, sekolah dilingkungan gereja, penginjilan, dan kontekstualisasi sehingga diharapkan gereja kembali mengalami zaman kejayaanya.